Effects of mixed-reality on players’ behaviour and immersion in a cultural tourism game: A cognitive processing perspective - Raptis, George E.; Fidas, Christos; Avouris, Nikolaos (International Journal of Human-Computer Studies, 2018)
Mixed-reality environments introduce innovative human-computer interaction paradigms assisted by enhanced visual content presentation which require from end-users to perform excessive cognitive tasks related to visual attention, search, processing, and comprehension. In such visually enriched interaction realms, individual differences in perception and visual information processing might affect users’ behaviour and immersion, given that such effects are known to exist in conventional computer environments, like desktop or mobile. In an attempt to shed light on whether, how, and why such effects persist within mixed-reality contexts, we conducted a between-subjects eye-tracking study (N=73) in which users interacted within either a conventional or a mixed-reality technological context, and adopted an accredited cognitive style theory to interpret the derived results. Analysis of results yielded that mixed-reality interaction realms amplified the effects of human cognitive style towards game-specific interaction behaviour and visual behaviour. Findings further support the added value of incorporating human cognitive factors in both design and run-time, aiming to provide adaptive and personalised features to end-users within mixed-reality interaction contexts. Such practical implications are also discussed in this paper.